Establishment of a dual-color fluorescence tracing orthotopic transplantation model of hepatocellular carcinoma - CHEN, QIAN (Mol Med Rep, 2016)
Different experimental models of hepatocellular carcinoma (HCC) have been used to investigate the biological mechanisms of hepatocarcinogenesis and its progression. However, previous studies have highlighted the difficulty of distinguishing between the tumor cells and stroma in experimental models of HCC. Therefore the aim of the present study was to establish a red-green dual-color fluorescence tracing orthotopic transplantation model of HCC, and investigate its practical values. Stable high red fluorescent protein (RFP)-expressing HepG2 human hepatoma cells and Hepa1-6 mice hepatoma cells were injected into the right liver lobe of green fluorescent protein-expressing nude mice. The growth and metastasis of the tumors were visualized using a whole-body in vivo fluorescence imaging system in real time. HCC tissues were extracted from tumor-bearing mice, and cut into 5-µm serial frozen slices. The organizational structure of the transplanted tumors was observed under a microscope. A dual-color fluorescence tracing orthotopic transplantation tumor model of HCC was successfully established with a success rate of 100%. The growth and metastasis of the tumors were visualized at each stage of development in the tumor-bearing mice. Tumor cells with red fluorescence and host cells with green fluorescence were identified to merge in the reconstruction region of tumor tissue. The invasion, migration, and cell fusion between tumor and host cells was observed clearly. The dual-color fluorescence tracing ortho-topic transplantation model of HCC was determined to be a stable and reliable method for tracking tumor progression. Mutual interactions between hepatoma cells and host tissues may be observed directly using this model, further elucidating the development of the tumor microenvironment.